2005
DOI: 10.1097/01.pcc.0000154960.59452.06
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function and ioduria in infants after cardiac surgery: Comparison of patients with primary and delayed sternal closure

Abstract: Patients with DSC compared with patients with primary sternal closure display more profound thyroid suppression in the immediate postoperative period. The use of povidone-iodine adhesive drapes with single povidone-iodine mediastinal irrigation in patients with DSC is associated with significant iodine absorption but no significant thyroid dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Likewise, we did not find an association between DSC and hypothyroidism on multivariate analysis. Although a previous study reported such an association [ 17 ], that study did not control for underlying morbidity or renal function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, we did not find an association between DSC and hypothyroidism on multivariate analysis. Although a previous study reported such an association [ 17 ], that study did not control for underlying morbidity or renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Neonates with congenital heart disease (CHD) represent an especially vulnerable group, because they have a higher frequency of congenital morphological defects of the thyroid gland [ 9 , 10 ], are routinely exposed to excess iodine, and are at risk of neurodevelopmental disabilities [ 11 , 12 ]. Sources of excess iodine exposure in infants with CHD include iodinated contrast media (ICM) administered during radiological procedures and topical iodine-containing antiseptics and iodine-impregnated dressings applied to chest wounds in the setting of delayed sternal closure (DSC) after cardiac surgery [ 13 17 ]. An injection of 3 to 5 mL/kg of Optiray 350 during cardiac catheterization, for example, contains 350 mg/mL of organically bound iodine and provides an iodine load far greater than the tolerable upper limit of 200 µg/day for infants 1 to 3 years of age [ 18 ].…”
mentioning
confidence: 99%
“…Of these, one developed severe primary hypothyroidism requiring treatment, the second resolved after transient treatment, and the third resolved spontaneously (23). Other studies have shown that the use of povidone-iodine irrigation in association with delayed sternal closure did not lead to any significant alteration in thyroid function (2426). Further studies are needed to assess the need for monitoring thyroid function after cardiac angiography or prolonged exposure to iodine-containing antiseptics.…”
Section: Iodine-induced Hypothyroidismmentioning
confidence: 91%
“…The evidence for iodine absorption of most of these studies includes documented serum iodine concentration and thyroid function abnormalities. Kovacikova et al (2005) investigated thyroid function and ioduria in infants after cardiac surgery with primary sternal closure compared with delayed sternal closure (DSC) and the exposure to povidone iodine for sternal wound protection. The patients with DSC display more profound thyroid suppression in the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 99%